2019
DOI: 10.1186/s12888-019-2085-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Mental Health First Aid training improve the mental health of aid recipients? The training for parents of teenagers randomised controlled trial

Abstract: Background There is well-established evidence that Mental Health First Aid (MHFA) training improves knowledge about how to support someone developing a mental health problem, but less evidence that this support improves the mental health of the recipient of aid. This randomised controlled trial aimed to assess the long-term effects of MHFA training of parents on the mental health of their adolescent children. Methods 384 Australian parents of an adolescent aged 12–15 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 22 publications
(28 reference statements)
1
56
0
Order By: Relevance
“…As with earlier follow-ups, there remained a lack of statistical power at 3-year follow-up. Even though there were higher rates of adolescents with mental health problems at 3-year follow-up (reflecting the higher risk period of middle-to-late adolescence), there was more attrition compared to 1-and 2-year follow-up [14]. There were few improvements in study outcomes observable 3 years after training, apart from parents' knowledge of youth mental health problems and adolescents' perceptions of general social support from their parents.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…As with earlier follow-ups, there remained a lack of statistical power at 3-year follow-up. Even though there were higher rates of adolescents with mental health problems at 3-year follow-up (reflecting the higher risk period of middle-to-late adolescence), there was more attrition compared to 1-and 2-year follow-up [14]. There were few improvements in study outcomes observable 3 years after training, apart from parents' knowledge of youth mental health problems and adolescents' perceptions of general social support from their parents.…”
Section: Discussionmentioning
confidence: 90%
“…Study methods have been described in detail elsewhere [14] but are briefly described here. The study was an RCT with participants randomized to Youth MHFA (YMHFA) or Red Cross Provide First Aid (PFA) training.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Communities play a large role in mental health care in lower and middle income countries [60,61] and partnership with communities is a strategy that has been successfully employed in Malaysia to improve mental health [62]. Training community members to provide initial help to people with mental disorders helps improve confidence, intention to help others and helping behaviours, however it is not yet clear whether these programs help improve mental health outcomes in people with mental health problems [63][64][65]. A systematic review of religious interventions concluded that they were effective [66] and in Malaysia religious professionals and traditional healers sometimes refer patients to services if they feel that the problem is a mental health concern, rather than a spiritual issue [19].…”
Section: Collaboration With People Outside the Hospitalmentioning
confidence: 99%